ASSESMEN KONTEN ISI BIDANG STUDI - Juhairiyah Juhairiyah (Nurul Jadid University, 2017)
Assessment is an important element of teaching and learning process, because it is able to contribute to the effectiveness of learning. Assessment is a continuous process, because it is an integral part of the overall educational experience for children. Improved learning will continue to occur when the choice of learning experience, and monitoring techniques for student experiences, is meticulously and precisely implemented. Assessment of learning outcomes of learners include; competence of attitudes, knowledge, and skills, performed in a balanced manner, so that it can be used to determine the relative positions of learners. The post-learning attitudes of the students must show the differences; better than the attitude of students before experiencing the learning process. This change is one indicator of the success of educators in implementing the teaching and learning process. Related psychomotor domain, the aspects that are considered by educators in conducting the assessment are; reading skills, writing skills, thinking skills ie; connecting something, associating and cultivating.